Sphingosine 1‐phosphate receptor 1 is required for retinal ganglion cell survival after optic nerve trauma. Issue 4 (6th July 2016) - Joly, Sandrine; Pernet, Vincent
Abstract: In this study, we used a classical optic nerve injury model to address the function of the sphingosine 1‐phosphate (S1P)–S1P receptor (S1PR) axis in retinal ganglion cell (RGC) death and axonal growth. After lesion, the expression of S1PR1 was generally reduced in axotomized RGCs but persisted in αRGCs, a subpopulation of injury‐resistant RGCs. Silencing S1PR1 with an adeno‐associated virus serotype 2 (AAV2) containing a shRNA specific to S1PR1 (AAV2.shRNA‐S1PR1) exacerbated the loss of RGCs induced by optic nerve crush; the rate of RGC survival was decreased by more than 24% in retinae infected with AAV2.shRNA‐S1PR1 compared with AAV2.shRNA‐scrambled or AAV2.GFP control treatments. In the superior and temporal regions of the retina, cell death rose by more than ~ 35% and ~ 50%, respectively, in comparison with control groups. In the optic nerve, S1PR1 silencing markedly reduced axonal sprouting after the lesion relative to control animals. Early after optic nerve crush, 67% of αRGCs stained for osteopontin were lost in retinae infected with AAV2.shRNA‐S1PR1, whereas the number of intrinsically photosensitive RGCs expressing melanopsin, another injury‐resistant RGC type, was not affected. Moreover, retinal infection with AAV2.shRNA‐S1PR1 down‐regulated mammalian target of rapamycin pathway activation in αRGCs. Together, our results reveal that S1PR1 contributes to survival and growth mechanisms in injured RGCs by regulating the mammalian target of rapamycin pathway. The role of sphingosine 1‐phosphate receptor 1 (S1PR1) was studied in retinal ganglion cell survival and axonal growth after optic nerve injury. After axonal damage, S1PR1 expression was decreased in retinal neurons. Viral‐mediated S1PR1 down‐regulation enhanced injury‐induced cell death and reduced spontaneous axonal growth. In injury‐resistant retinal neurons, the activation of mTOR signalling was down‐regulated by silencing S1PR1, suggesting an important role for S1PR1 in neuronal growth and survival mechanisms in vivo . Abstract : The role of sphingosine 1‐phosphate receptor 1 (S1PR1) was studied in retinal ganglion cell survival and axonal growth after optic nerve injury. After axonal damage, S1PR1 expression was decreased in retinal neurons. Viral‐mediated S1PR1 down‐regulation enhanced injury‐induced cell death and reduced spontaneous axonal growth. In injury‐resistant retinal neurons, the activation of mTOR signalling was down‐regulated by silencing S1PR1, suggesting an important role for S1PR1 in neuronal growth and survival mechanisms in vivo .